Big Data Application for Traffic Estimation on a Website: Big Daddy Case - Udairaj Singh, Shubham; Banelienė, Rūta (Vilnius University Proceedings, 2023)
While living under rapidly changing conditions innovation, flexibility and readiness to change are grounding prosperity of the firm. But any changes for companies should be reasoned and made on the basis of analytical approach. Big data usually could help in this situation without spending time and money on expensive research activities. Therefore, this paper is focused on big data application on customers’ behavior switching from one product to new its look. Modeling is based on few monthsˈ daily data with application of regression analysis and the least squares method. The major finding comes up with the estimation output that the new webpage is more popular among IOS and WEB users, although Android systems showing negative impact on switching to new website